(3GdCJQGc aj eUQ hJQGKge GdKbGajs (3OQGSI JMdjdjI hKHJ HHdjhZQGaj dEQKge GdeWHhY efP YgO eMeO Ydjs - (3ChZdj, Cced GdOjf EMSGfs; (3CQOhZGf, QLH WjHs; (3SYOGhj, UGdMs ((3GdbGgQIs (3OGQ GdTQhbs, 2011)
(3cJH QLH WjH CQOhZGf (B: (3gPg GdOQGSI GdJj JYO GdChdi aj eLGdgG JHjf dfG HhVhM Edi Ci eOi jQJHW eUjQ JQcjG HeUjQ eUQ hEdi Ci eOi jQJHW eUjQ ESJGfHhd HeUjQ GdbGgQI (B. . . (3hCQGfj Ydi KbI HCf gPG GdYed GdPj Hjf CjOjfG Sha jSge HTcd LGO aj OYe Jdc GdYdGbGJ hjbQH GdeSGaGJ Hjf GdTYHjf CcKQ hCcKQs
1 4 12 13
Keywords: (3eUQs -- (3JGQjNs -- (3YUQ eMeO Ydj (B1805 - 1849s; (3eUQs -- (3JGQjNs -- (3GdYUQ GdMOjKs